QUANTITATIVE FITNESS FOR SERVICE ANALYSIS OF DENTED PIPELINE CAUSED BY DROPPED SHIPâS ANCHOR CASE STUDY: OFFSHORE GAS PIPELINE IN JAKARTA BAY - Odasse Krid, Hizkia
Oil and gas industry has an important role in driving the economy in Indonesia. Infrastructure in this industry needs to be ensured to work in safe conditions to prevent failures. Pipeline is one of the infrastructures that is often used in the oil and gas industry. Any types of accidents can happen to this pipeline. One of the accidents that are often found in offshore pipelines is anchoring. This accident can cause dents and highly happen by the pipelines that located in high ship traffic areas such as the area around the port. Fitness for service analysis of the dented pipeline in Jakarta Bay is to be discussed in this undergraduate thesis. This pipeline was chosen as a case study because it is located near to ports, namely Muara Baru Port, Muara Karang Port, and Tanjung Priok Port. Finite element analysis method is utilized to determine the dent caused by ship anchoring. The analysis is conducted using Fitnessfor- Service assessment method contained in API 579-1/ASME FFS-1. In addition, a parametric study was also carried out to determine the effect of sea depth on the depth of the dent. In addition, parametric study was also carried out to determine the effect of sea depth on dent depth and the effect of corrosion on stress concentration and the fitness for service status of pipeline. The result of the Fitness-for-Service assessment shows that the pipeline is not in a permissible condition for the case ships with DWT more than 45,000 tons. For other cases, the status is still in acceptable condition, so it is permitted to operate normally. Parametric studies indicate that the ocean depth has an impact on the dent depth, in accordance with the average anchor ship's terminal velocity characteristics achieved at a depth of 10 meters. Parametric studies on corrosion show that corrosion at position one has the highest influence on stress concentration, increasing by up to 15% for a corrosion depth of 50%. Corrosion at position one also affects the fitness for service status of the pipeline for a corrosion depth ranging from 30% to 50%.